How Joseph Fowler Read his Hebrew Bible. Issue 1 (15th September 2020) - Hardy, John Christopher
Abstract : How did a work-a-day Victorian Hebraist read the Hebrew Bible? Suggestive information on the subject is found in the unpublished memoirs of Canon Dr Joseph Thomas Fowler (1833–1924), Durham Hebraist and antiquarian. Interesting as an example of contemporary devotional practice among Durham-based and Durham-trained Anglican clergy, Fowler's Hebrew Bible reading habit also illustrates the informal aspect of his working relationships with colleagues in the fledgling university of Durham. This article offers, too, a frame of reference, by exploring Fowler's biography, his Durham undergraduate career (1858–1861), and his work as university Hebrew lecturer for almost half a century (1871–1917). Incidental light is shed on the ecclesiastical ethos, the staff, the curriculum, and the pedagogy of Durham University in the mid-nineteenth century.